2014
DOI: 10.1002/2014jd021641
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the sources and evolution processes of severe haze pollution in Beijing in January 2013

Abstract: China experienced severe haze pollution in January 2013. Here we have a detailed characterization of the sources and evolution mechanisms of this haze pollution with a focus on four haze episodes that occurred during 10-14 January in Beijing. The main source of data analyzed is from submicron aerosol measurements by an Aerodyne Aerosol Chemical Speciation Monitor. The average PM1 mass concentration during the four haze episodes ranged from 144 to 300 μg m À3, which was more than 10 times higher than that obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
491
3
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 693 publications
(563 citation statements)
references
References 63 publications
59
491
3
4
Order By: Relevance
“…Theoretically, its absorption properties can be significantly enhanced by internal mixing with other compounds because the coatings act as a lens and 5 enlarge its mass absorption cross section effectively (Bond et al, 2013;Chen et al, 2017a). We analyzed this absorption amplification effect based on the consistent in-situ measurements during the development of severe haze pollution in Beijing in January 2013 (Sun et al, 2014). Compared with clean period, the secondary aerosol increased significantly during haze episodes.…”
Section: Amplified Dome Effect By Mixing With Scattering Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, its absorption properties can be significantly enhanced by internal mixing with other compounds because the coatings act as a lens and 5 enlarge its mass absorption cross section effectively (Bond et al, 2013;Chen et al, 2017a). We analyzed this absorption amplification effect based on the consistent in-situ measurements during the development of severe haze pollution in Beijing in January 2013 (Sun et al, 2014). Compared with clean period, the secondary aerosol increased significantly during haze episodes.…”
Section: Amplified Dome Effect By Mixing With Scattering Aerosolsmentioning
confidence: 99%
“…During hazy days, concentration of BC, one of the most important aerosol components from both environmental and climate perspectives, could exceed 20 μg m -3 in China's megacities (Yang et al, 2007;Sun et al, 2014), far more than those in other regions across the world. Such a high level of BC concentration in China is primarily attributed to intensive residential combustions and coal-dominant energy structure (Qin and Xie, 2011;Zhang et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…14 C results indicated that the contribution of biomass-burning and biogenic emissions to the WINSOC and EC accounted for 63% and 48%, respectively, which was 10% lower than the south wind. In recent years, the BTH region has been considered as the most severely polluted area in China and industrial emissions, coal burning and automobile emissions are considered as major contributors (Pui et al, 2014;Sun et al, 2014). The high contribution of biomass-burning emission suggests weak impact of carbonaceous aerosols emitted from the BTH region on the air quality at the sampling site.…”
Section: Intraday Fluctuation Of Tsp Pm 25 and Carbonaceous Speciesmentioning
confidence: 99%
“…This technique has advantages such as high sensitivity, cost efficiency, easy control, and a long effective absorption optical path. The CAPS instrument measures the phase shift of a distorted waveform of the modulated light from a light emitting diode (LED) in a sample cell with two high reflectivity mirrors (Sun et al, 2014). It has a demonstrated sensitivity of less than 2 Mm −1 for 1 s sampling periods.…”
Section: Capsmentioning
confidence: 99%